BAKTI SOSIAL CINTA KASIH UNTUK MEMBANTU KELUARGA PRASEJAHTERA DI KOTA TEBING TINGGI - Rakhmawati Purba; Rahmah Hidayati; Nurmayladzi Laisa; Safira Tania; Aurelia Sekar Rini; Juwita Juwita; Abednego Ketaren; Rizki Wulanita Batubara; Rumiris Siahaan; Tiara Adriani (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2024)
Economic problems are one of the problems that people often face today, both in urban and rural areas. This condition can of course have an influence on their social life and daily activities. Social service is a social service activity that is a form of humanity between people in order to create a sense of love, a sense of helping each other, a sense of mutual care for people who need a helping hand from various parties. The Buddhist Tzu Chi Foundation carried out social service activities providing charity food assistance for the umpteenth time in the city of Tebing Tinggi. Focusing on underprivileged communities in the Persikan and Tualang sub-districts as well as janitors and street sweepers, scavengers who depend on their livelihoods at the Tebing Tinggi TPA based on a survey conducted previously with the help of Tzu Chi Buddhist Volunteers and Volunteers guided by good government officials from Padang Hulu District and Tualang and Persikan Subdistricts along with hamlet heads and local communities. The activity was right on target because before the distribution of basic necessities a survey had been carried out at houses with predetermined criteria and during the implementation it went in an orderly and smooth manner without any problems, because it had gone through the briefing and direction stages for 130 volunteers and volunteers.